"SHORTCUT" Audio Sampling and Foley Techniques as Techniques for Producing Sound Banks in Electronic Music Production Future Bass - Ayubi, Ariza Fabiano; HR, Hafir; Nel, Yusnelli (Scoring: Journal of Film Music, 2023)
Abstrak"Jalan Pintas" merupakan karya musik yang berangkat dari keluh kesah atau kegelisahan diri sendiri. Sebuah karya musik dengan bentuk song writing dimana terdapat sebuah pengolahan sampel suara (sound design) untuk menghasilkan sebuah materi suara (Sound Bank) yang diproduksi dengan teknik audio sampling dan foley. Sound Bank yang digunakan dalam produksi musik karya ini diproduksi menggunakan pendekatan teknik Audio Sampling dan Foley. Tujuannya untuk memperkuat lirik yang disertakan dengan video clip.Abstract"Shortcut" is a piece of music that departs from one's own worries or anxieties. A piece of music in the form of songwriting where there is sound sample processing (sound design) to produce sound material (Sound Bank) which is produced using audio sampling and foley techniques. The Sound Bank used in the music production of this work was produced using the Audio Sampling and Foley technique approach. The goal is to strengthen the lyrics included in the video clip.